Assessing the impact of aquifer-eustasy on short-term Cretaceous sea-level. (August 2020) - Davies, Andrew; Gréselle, Benjamin; Hunter, Stephen J.; Baines, Graham; Robson, Chris; Haywood, Alan M.; Ray, David C.; Simmons, Michael D.; van Buchem, Frans S.P.
Abstract: The origin of moderate magnitude (tens of metres), short-term Cretaceous eustatic cycles remains enigmatic. The historical view of ubiquitous Cretaceous warmth casts doubt on the presence of significant terrestrial ice caps and the role of glacio-eustasy. As such, aquifer-eustasy is increasingly advocated as the primary driver of Cretaceous short-term sea-level change. Here, we analyse the role of aquifer-eustasy in driving Cretaceous short-term cycles by assessing the spatio-temporal pattern of aridity and humidity under differing CO2 forcing in new climate simulations for the Valanginian, Turonian, and Maastrichtian. Elevated CO2 forcing acts to increase the spatial extent of fully arid land areas, while resulting in only a marginal expansion of fully humid zones. Consequently, the greatest aquifer charge is more likely during lower CO2 /cooler intervals, indicating that aquifer-eustasy works in phase with both glacio- and thermo-eustasy in contrast to the current aquifer-eustasy paradigm. Modern data indicate that climate is a primary control on water table depth. Using this constraint, the hydrological response in our Cretaceous simulations to large changes in atmospheric CO2 are insufficient to generate reported eustatic magnitudes. Our most likely aquifer-eustasy estimates are decimetre scale. Even using optimistic values for the impact of lakes and assuming the water table depth was reduced from the modern average to 0 m globally, the total aquifer-eustasy response remains smaller than 5 m. Our results indicate that glacio-eustasy was the most likely driver of Cretaceous short-term cycles, consistent with a growing body of evidence that challenges the ubiquitously warm Cretaceous notion.